Proteins associated with quality deterioration of prepared chicken breast based on differential proteomics during refrigerated storage. (22nd December 2020) - Luo, Xin; Dong, Kai; Liu, Lan; An, Fengping; Tang, Daobang; Fu, Lingyun; Teng, Hui; Huang, Qun
Abstract: BACKGROUND: Prepared chicken breast deterioration is a complex biochemical process, of which protein change is one of the main features. The present research focuses on the analysis of proteins related to the deterioration in quality of prepared chicken breast through differential proteomics analysis. RESULTS: The physicochemical indexes of prepared chicken breast showed that quality gradually decreased at the second week of refrigerated storage, while the deterioration of chicken breast meat was obvious at the third week. Three key time points of quality change were determined to be at 0th, 2th and 5th week, respectively. In addition, 39 differential proteins were successfully identified using two‐dimensional gel electrophoresis and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. Most of the identified proteins showed significant differences in expression at the three key points of storage, of which actin, myosin, α‐1, 4‐glucan phosphorylase, phosphoglucomutase 1, heat shock protein β‐1, tubulin β‐7 chain and skeletal muscle type tropomodulin (fragment) were closely related to the quality deterioration of prepared chicken breast, and thus potential indicator proteins to evaluate the quality of chicken breast. CONCLUSION: The current study indicated that the physicochemical quality of prepared breast notably changed during refrigerated storage. Three key time points of quality change in the storage process of prepared chicken breast were determined. Furthermore, differential proteomics identified the key proteins related to freshness, which provides a theoretical basis for exploring the mechanism of chicken breast deterioration. © 2020 Society of Chemical Industry